The Transcriptome Analysis Provides New Insights into Signaling for Bamboo Shoot Development of Sympodial Bamboo - Shunkai Hu; Mengran Dong; Qirong Guo (Foods)
Bamboo is a member of the Poaceae family and serves as an important economic resource with various applications, including reforestation, food production, and environmental conservation, due to its rapid growth and renewable nature. Among its various uses, bamboo shoots stand out for their tender texture and delicate flavor, making them a highly sought-after culinary delicacy in many cultures and a key ingredient in global food industries. Despite extensive research on the development of monopodial bamboos, studies focused on the developmental processes of sympodial bamboos, especially regarding their culinary potential, remain limited. This study conducted a comprehensive transcriptomic analysis of sympodial bamboo (Bambusa sp.) across six developmental stages (S1–S6) to uncover the molecular regulatory networks governing early bamboo shoot development. The results revealed that 1603 common differentially expressed genes (DEGs) across S1–S6 were enriched in multiple key pathways, with the most significant being plant hormone signaling, MAPK signaling, and Glycolysis/Gluconeogenesis pathways. Co-expression clustering analysis indicated that the Glycolysis/Gluconeogenesis pathway plays a crucial role during the later stages of bamboo shoot development (S5–S6), impacting its texture and flavor—two critical factors determining its culinary quality. Further Weighted Gene Co-expression Network Analysis (WGCNA) highlighted the significant role of the MAPK signaling pathway during early bamboo shoot development and identified key hub genes (MKK, MPK, MEKK) within this pathway, emphasizing their importance in cell division and hormonal coordination. This study provides valuable insights into the molecular mechanisms underlying the rapid growth and exceptional flavor of bamboo shoots and lays the foundation for the genetic improvement of bamboo as a sustainable and nutritious food source, enhancing its value as a premium food ingredient in the global market.